2019
DOI: 10.1039/c8fo02248h
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Calcineurin-NFAT pathway mediates the effect of thymol on oxidative metabolism and fiber-type switch in skeletal muscle

Abstract: Thymol is a major component of thyme, and it has been reported that thymol administration reduces body weight, plasma insulin and blood glucose in type-2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…To better understand the pathway through which EA affects myofibre transition, we examined several potential signalling pathways, including p38 MAPK, PGC‐1α, PPAR‐δ and calcineurin‐NFAT (Luo et al, 2019; Montaigne et al, 2021; Xue et al, 2021), observing that EA significantly inhibited the phosphorylation of p38 MAPK, but had minimal effect on other signalling pathways (Figure 6a,b). An increase in DUSP1 at both the protein (Figure 6c) and gene ( p = 0.0228, ST36 vs. EA Con, Figure 6d) levels after EA treatment was also observed.…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the pathway through which EA affects myofibre transition, we examined several potential signalling pathways, including p38 MAPK, PGC‐1α, PPAR‐δ and calcineurin‐NFAT (Luo et al, 2019; Montaigne et al, 2021; Xue et al, 2021), observing that EA significantly inhibited the phosphorylation of p38 MAPK, but had minimal effect on other signalling pathways (Figure 6a,b). An increase in DUSP1 at both the protein (Figure 6c) and gene ( p = 0.0228, ST36 vs. EA Con, Figure 6d) levels after EA treatment was also observed.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, an increase in NFATc1 protein expression was induced by alternating the slow muscle fibre type (Schulz & Yutzey, 2004). Furthermore, increased calcineurin protein expression via increased nerve activity was induced by increased NFATc1 protein expression (Baldwin et al, 2013;Luo et al, 2019). Therefore, R30 supplementation may attenuate the HU-related slow-to-fast fibre type shift possibly via R30-induced activation of the calcineurin-NFAT signalling pathway, independent of the protein expression level of PGC-1α.…”
Section: Discussionmentioning
confidence: 99%
“…the typology of whole muscle fibres from slow-to fast-twitch fibres following disuse. Moreover, it has been suggested that activating the nervous system induces fibre type shifts via the calcineurin-nuclear factor of activated T-cells (NFAT) pathway, which is another regulator of fibre type shift (Luo et al, 2019). Certain lactic acid bacterial strains stimulate the autonomic nervous system via the central nervous system, and each strain has distinct effects (Horii et al, 2014;Yamano et al, 2006).…”
Section: New Findingsmentioning
confidence: 99%
“…Furthermore, the activation of NFAT molecule follows the activation of Ca 2+ /calmodulin dependent phosphatase, while in T cells, the level of free Ca 2+ is higher, so the activity of Ca 2+ /calmodulin dependent phosphatase increases, and NFAT can maintain the activation state in the nucleus for a long time and promote the transcription of some genes. In addition to Ca 2+ /calmodulin dependent phosphatase, there are many proteins and signaling pathways that regulate NFAT, such as T cell receptor (TCR) cross-linking ( 49 51 ). Moreover, the activation of Lck and ZAP70 leads to calcium mobilization in T cells, which leads to NFAT-dependent reporter gene expression ( 52 ).…”
Section: Discussionmentioning
confidence: 99%